2011
DOI: 10.1002/dmrr.1262
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of microRNA miR‐326 in type 1 diabetic patients with ongoing islet autoimmunity

Abstract: In conclusion, we have shown that miR-326 is expressed at higher levels in T1D subjects with ongoing islet autoimmunity, similar to what has been observed in multiple sclerosis, in which levels of this microRNA were highly correlated with disease severity. Interestingly, an online search of miR-326 predicted targets revealed vitamin D receptor and Erythroblastosis virus E26 oncogene homologue 1, two molecules highly involved in immune regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(95 citation statements)
references
References 20 publications
1
88
0
2
Order By: Relevance
“…Elevated expression of miR-326 was found in peripheral blood lymphocytes of T1D patients with ongoing islet autoimmunity (Sebastiani et al 2011). Clinically, Nielsen et al (2012) showed the upregulation of twelve serum miRNAs (miR-152, miR30a-5p, miR-181a, miR-24, miR-148a, miR-210, miR-27a, miR-29a, miR-26a, miR-27b, miR-25, and miR-200a) in T1D patients; particularly they found that miR-25 was negatively associated with b-cell function.…”
Section: Pkb (Akt) Signaling (Insulin Sensitivity)mentioning
confidence: 99%
“…Elevated expression of miR-326 was found in peripheral blood lymphocytes of T1D patients with ongoing islet autoimmunity (Sebastiani et al 2011). Clinically, Nielsen et al (2012) showed the upregulation of twelve serum miRNAs (miR-152, miR30a-5p, miR-181a, miR-24, miR-148a, miR-210, miR-27a, miR-29a, miR-26a, miR-27b, miR-25, and miR-200a) in T1D patients; particularly they found that miR-25 was negatively associated with b-cell function.…”
Section: Pkb (Akt) Signaling (Insulin Sensitivity)mentioning
confidence: 99%
“…28,62 miR-326 expression is significantly increased in peripheral blood mononuclear cells (PBMCs) from T1D patients; the elevated levels correlate with ongoing islet autoimmunity and the disease severity. 63 Several possible target genes of miR-326, including vitamin D receptor and erythroblastosis virus E26 oncogene homolog 1, are vital modulators of the immune system, suggesting that the miRNA probably has important effects on autoimmunity in T1D by targeting these genes. 63 Another study performed by Yang et al 64 identified 26 differentially expressed miRNAs in PBMCs from newly diagnosed T1D patients, among which miR-146 was the most downregulated molecule.…”
Section: Mirnas: Regulators Of Immune Pathogenesis In T1dmentioning
confidence: 99%
“…63 Several possible target genes of miR-326, including vitamin D receptor and erythroblastosis virus E26 oncogene homolog 1, are vital modulators of the immune system, suggesting that the miRNA probably has important effects on autoimmunity in T1D by targeting these genes. 63 Another study performed by Yang et al 64 identified 26 differentially expressed miRNAs in PBMCs from newly diagnosed T1D patients, among which miR-146 was the most downregulated molecule. The study also showed that the miR-146 levels were associated with ongoing islet autoimmunity.…”
Section: Mirnas: Regulators Of Immune Pathogenesis In T1dmentioning
confidence: 99%
See 1 more Smart Citation
“…Levels of miR-326 were measured in peripheral blood lymphocytes from type 1 diabetic patients [49]. Note that these miRNAs were extracted from whole blood samples and were in fact associated with blood cells.…”
Section: Circulating Mirnas As Biomarkers Of the Disease Processmentioning
confidence: 99%